In‐Depth Proteome Analysis of Ricinus communis Pollens. Issue 3 (14th December 2018) - Teixeira, Fabiano M.; Shah, Mohibullah; Domont, Gilberto B.; Nogueira, Fábio C.S.; Campos, Francisco A.P.
Abstract: Pollen grains are tiny structures vital for sexual reproduction and consequently seed and fruit production in angiosperms, and a source of many allergenic components responsible for deleterious implications for health worldwide. Current pollen research is mainly focused on unraveling the molecular mechanisms underlying the pollen germination and tube formation passing from the quiescent stage. In this context, an in‐depth proteome analysis of the pollens from Ricinus communis at three different stages—that is, mature, hydrated, and in vitro germinated—is performed. This analysis results in the identification of 1950 proteins, including 1773, 1313, and 858, from mature, hydrated, and germinated pollens, respectively. Based on label‐free quantification, 164 proteins are found to be significantly differentially abundant from mature to hydrated pollens, 40 proteins from hydrated to germinated, and 57 proteins from mature to germinated pollens, respectively. Most of the differentially abundant proteins are related to protein, carbohydrate, and energy metabolism and signaling. Besides other functional classes, a reasonable number of the proteins are predicted to be allergenic proteins, previously undiscovered. This is the first in‐deep proteome analysis of the R. communis pollens and, to the best of our knowledge, one of the most complete proteome dataset identified from the pollens of any plant species, thus providing a reference proteome for researchers interested in pollen biology.